A Model for Enhancing Community Economic Resilience in the VUCA Era from a Public Management Perspective - Haris Wanto, Alfi (Iapa Proceedings Conference, 2025)
The VUCA era—characterized by volatility, uncertainty, complexity, and ambiguity—has reshaped the global socio-economic environment. Economic instability, rapid technological shifts, and political dynamics require communities to build adaptive and resilient economic systems. In this context, public management plays a strategic role in driving inclusive and responsive policy frameworks. Failure to effectively address VUCA-related challenges may weaken societal capacity to sustain long-term economic well-being. This study employs a qualitative approach with an exploratory case study method. Data were collected through in-depth interviews, participatory observations, and policy document analysis across selected regions in Indonesia that have demonstrated strong economic resilience. Thematic triangulation was used to identify emerging patterns of capacity building among communities and public institutions. The research focused on the interaction between government policies, grassroots initiatives, and civic participation in developing a sustainable resilience model. The findings reveal that community economic resilience is strongly supported by transformative public leadership, robust local institutional networks, and flexible policy support. The proposed model underscores the importance of collaborative governance, adaptive learning, and community-based empowerment. The study recommends developing participatory and locally-informed public policies to foster sustainable economic systems capable of navigating the complexities of the VUCA era.